Formal defenses in the administrative case and its relationship to the substantive defenses in Jordan - Al rhamnah, Khaleel Suliman Khaleel (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aims to clarify the formal defenses in the administrative case, and their relationship to the substantive defenses in Jordan in the absence of a law governing administrative litigation procedures, given that the Jordanian Administrative Judiciary Law No. 27 of 2014 referred the litigation procedures before the administrative judiciary to the Civil Procedure Code in what was not mentioned in it. A text in the Administrative Judiciary Law, and in a manner that does not conflict with the nature of the administrative lawsuit, which is characterized by a special nature that differs from the civil judiciary, and therefore the research problem lies in the absence of texts regulating the procedures of the administrative lawsuit in line with its nature. The administrative case, as well as the relationship of these defenses with the substantive defenses that relate to the origin of the right, and our difference between the defenses in the administrative case and the requests submitted by the litigants and the relationship of each to the other, as well as the role of the administrative judge in directing the lawsuit procedures, and we reached a set of results and recommendations represented in the need for a law regulating procedures Litigation before the administrative courts.
Keywords: defenses; requests; formal defenses; substantive defenses; administrative case